2022
DOI: 10.1111/maps.13938
|View full text |Cite
|
Sign up to set email alerts
|

The Winchcombe meteorite—A regolith breccia from a rubble pile CM chondrite asteroid

Abstract: The Winchcombe meteorite is a CM chondrite breccia composed of eight distinct lithological units plus a cataclastic matrix. The degree of aqueous alteration varies between intensely altered CM2.0 and moderately altered CM2.6. Although no lithology dominates, three heavily altered rock types (CM2.1-2.3) represent >70 area%. Tochilinite-cronstedtite intergrowths (TCIs) are common in several lithologies. Their compositions can vary significantly, even within a single lithology, which can prevent a clear assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
65
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(75 citation statements)
references
References 90 publications
10
65
0
Order By: Relevance
“…However, as a first approximation, Figure 6 can be used as a classification tool to define a subtype for a particular CM sample. As can be seen from Figure 6, there is good agreement between the petrologic subtypes for Winchcombe defined on the basis of mineralogical criteria (Suttle et al, 2022) and the subtype based on D 17 O composition.…”
Section: Oxygen Isotopesmentioning
confidence: 64%
See 1 more Smart Citation
“…However, as a first approximation, Figure 6 can be used as a classification tool to define a subtype for a particular CM sample. As can be seen from Figure 6, there is good agreement between the petrologic subtypes for Winchcombe defined on the basis of mineralogical criteria (Suttle et al, 2022) and the subtype based on D 17 O composition.…”
Section: Oxygen Isotopesmentioning
confidence: 64%
“…BM.2022, M1-85 (original mass 8.846 g) and BM.2022, M1-86 (original mass 6.931 g) were both recovered from the Wilcock family driveway and represent pieces from the main mass, which had a total recovered mass of ~320 g (King et al, 2022). In contrast, BM.2022, M9-18 ("Field Stone") comprises gram-sized interior chips recovered from the single 152 g fusion crusted stone located in the fields around Rushbury House Farm (Suttle et al, 2022). This stone broke during collection allowing interior material to be sampled.…”
Section: Methodsmentioning
confidence: 99%
“…However, this suggestion cannot be readily confirmed because none of the published petrologic classifications include all of the falls and finds discussed here. In addition, several of the falls are breccias containing clasts with different degrees of aqueous alteration (i.e., Aguas Zarcas, Kerraouch et al., 2021; Cold Bokkeveld, Lentfort et al., 2021; Winchcombe, King et al., 2022; Suttle et al., 2022). Thus, milligram‐size samples of the same meteorite may differ significantly in phyllosilicate abundance.…”
Section: Resultsmentioning
confidence: 99%
“…The classification of Winchcombe as a CM meteorite was based on general elemental abundances (King et al, 2022). Detailed scanning electron microscope energy dispersive x-ray analysis of Winchcombe samples (Suttle et al, 2023) has shown that several lithologies are present, with the most common ranging from CM2.0 (most processed) to CM2.5 (least processed). This is consistent with the results found here by the Raman analysis of the carbon bands, which produced results similar to those from the Murray meteorite (type CM2.4/2.5), and with the stepped combustion and pyrolysis-GC-MS data.…”
Section: Discussionmentioning
confidence: 99%